(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study aims to explore the impact of digitalisation on marketing. The advent of digitalisation has ushered in a new era in marketing, fundamentally transforming how businesses engage with consumers. This abstract explores the profound impact of digitalization on marketing practices, emphasizing its effects on consumer behaviour, marketing strategies, and the overall customer experience. Digitalisation has revolutionized consumer behaviour, with individuals increasingly relying on digital platforms, such as social media, search engines, and e-commerce websites, to gather information, make purchasing decisions, and interact with brands. This shift has created an abundance of data, enabling marketers to gain deeper insights into consumer preferences, needs, and behaviours. Marketers can now leverage analytics and data-driven tools to tailor marketing messages, personalize experiences, and target specific customer segments more effectively.